Modeling Of Beta-Lactamase Protein In Klebsiella Pneumoniae: In Silico Study - Naser Raheem, Noor; Jabbar Sattar, Rand; Majid Abdulhussein, Taif (Medical Science Journal for Advance Research, 2022)
Background: Klebsiella pneumoniae is a bacterium that normally lives inside human intestines, where it doesn't cause disease. But if K. pneumoniae gets into other areas of the body, it can lead to a range of illnesses, including pneumonia, bloodstream infections, meningitis, and urinary tract infections. The results that have been obtained from some servers that have been used in this study were gave a poor and good quality of prediction. SWISS MODEL server gave more promising results. Validation was done for the model study by using QMEAN score and ProSA server. 3D Refine and Mod Refiner were used for model refinement. Finally, ProSA server have been used in order to revalidate themodel. . Conclusion: SwissMODEL is a three-dimensional structure of an assumed protein sequence that was predicted via homology modeling, and this three-dimensional structure is based mostly on alignments to one or more proteins with known structures. Following construction of the model, it was evaluated and enhanced using 3D-Structure modeling software, which was developed by the University of California, San Francisco (UCSF).